Could slackline training complement the FIFA 11+ programme regarding training of neuromuscular control? - Jäger, T.; Kiefer, J.; Werner, I.; Federolf, P. A. (European Journal of Sport Science, 2017)
The current study compared changes in neuromuscular control between slackline training and the stabilization training elements of the FIFA 11+ programme. Twenty-five students in 2 groups performed a 12-unit training programme. The slackline training group (n = 13) exclusively trained with a slackline. The stabilization training group (n 12) practised exercises as described in the second part of the FIFA 11+ programme. Improvements in balance were assessed using three tests for dynamic, quasi-static, and perturbed postural control: the star excursion balance test (SEBT), the closed-eye single-leg stance, and the MFT S3-Check. Both groups significantly improved the stability and sensorimotor index of the MFT S3-Check (p < .001), their range on the SEBT (p < .001), and the duration of closed-eye single-leg stance (p < .001). The group × training interaction was significant for the MFT S3-Check (stability index: p = .042; sensorimotor index: p = .004) and the SEBT (dominant leg: p = .003; averaged both legs: p = .016), with the slackline training group showing a larger training effect than the stabilization training group. The results of the present study suggest that slackline training offers similar - or better - improvements in neuromuscular control as the FIFA 11+ warm-up programme. If compliance with the FIFA 11+ programme is declining, then slacklining might offer an alternative approach to reach the training goals of improved sensorimotor control.